The liver talks back: NPY orchestrates attraction of cancer cells and CHK2-dependent clonogenicity in the metastatic niche - Laura Wormser; Valerie Fritz; Melanie Kappelmann-Fenzl; Nicole Rachinger; Pol Escudé; Karin Enderle; Matthias D. Kaufmann; Miriam Düll; Abdo Mahli; Sebastian Zundler; Moritz Leppkes; Stefan Fischer; et al. (Proceedings of the National Academy of Sciences, 2025)
RNA interference (RNAi) therapeutics represent breakthrough discoveries, but their use in cancer remains limited due to hepatocyte-specific targeting. Cancer metastasis is regulated by complex crosstalk between tumor cells and niche-derived factors. However, the molecular mechanisms enabling metastatic seeding and outgrowth in the liver remain incompletely understood, representing a major clinical challenge. We identified neuropeptide Y (NPY) as a promotor of liver metastasis. Hepatocyte-derived NPY attracts metastatic tumor cells to the liver niche. Subsequent microenvironment activation induces TGFβ, promoting a vicious cycle of perimetastatic NPY secretion and liver metastasis. Concomitantly, cancer cells upregulate the NPY-5 receptor (Y5R) which is correlated with liver metastasis. NPY-Y5R crosstalk drives chemotactic migration via cAMP and ERK signaling. Moreover, NPY-Y5R activation dephosphorylates checkpoint kinase 2 to promote clonogenicity and proliferation of cancer cells. Lipid nanoparticles (LNPs) are a promising drug delivery vehicle for siRNAs. LNPs carrying siRNA pools targeting NPY were designed, and preclinical studies provided evidence for efficacy for the treatment of liver metastasis. Our findings transform the limitation of hepatocyte specificity of RNA interference into a therapeutic advantage, introducing a paradigm for the treatment of hepatic metastases.